2022
DOI: 10.1073/pnas.2201794119
|View full text |Cite
|
Sign up to set email alerts
|

GPR174 signals via Gαs to control a CD86-containing gene expression program in B cells

Abstract: SignificanceModeling immune responses in vitro is critical for studying many facets of the B cell response. We show that during culture without stimulation, mouse B cells undergo massive changes in gene expression. Many of these changes are promoted by GPR174 signaling via Gαs. GPR174 and Gαs also contribute to reduced B cell viability during culture. We suggest that GPR174 antagonists may be useful to reduce the shift in gene expression and to augment B cell survival during culture. We also provide evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…3E), including the genes encoding the major gut-homing integrin, integrin beta-7 (ITGB7), and—perhaps more unexpectedly—transcripts encoding the chylomicron apolipoprotein ApoE or the lysophosphatidylserine receptor Gpr174 (Fig. 3F), whose functions in B cells are not clear ( 45 ). The expression of some transcripts normalized after a day or two (module no.…”
Section: Resultsmentioning
confidence: 99%
“…3E), including the genes encoding the major gut-homing integrin, integrin beta-7 (ITGB7), and—perhaps more unexpectedly—transcripts encoding the chylomicron apolipoprotein ApoE or the lysophosphatidylserine receptor Gpr174 (Fig. 3F), whose functions in B cells are not clear ( 45 ). The expression of some transcripts normalized after a day or two (module no.…”
Section: Resultsmentioning
confidence: 99%
“…The distinctive G s engagement of GPR174 is totally out of our expectations. The extensive polar interactions between receptor/Gα s and the deepest insertion of αH5 into the intracellular core of the receptor suggest that GPR174 uses a unique way to bind and engage Gα s , and those observations also indicate that G s is tightly packed against receptor, and this may explain the high level of constitutive activity of GPR174 11,37 and weak ligand-induced G s dissociation activity (see the section "Methods" functional assay). We used the NanoBiT strategy in our complex assembling, the strategy only increases the local concentration of binding partners and cannot force an interaction that does not exist in nature, evidenced by the identical structures of GPR110/G s complexes solved with or without the NanoBiT strategy recently 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…253 Interestingly, very recently, it has also been demonstrated that in vivo, lyso-PS acts via GPR174-Gα s G-proteins to also promote the expression of CD86 on B cells, thereby fine-tuning B cell responses during conditions of inflammation. 255 While the direct involvement of lyso-PS in some immunological processes has not yet been proven, GPR174's role in these processes has now been well-established. For example, the loss of GPR174 in mice prevents the progression of sepsis and the cytokine storm associated with it.…”
Section: G-protein Coupled Receptor 174 (Gpr174)mentioning
confidence: 99%